The protective effect of hydroalcoholic extract of Ephedra pachyclada leaves on ovarian damage induced by cyclophosphamide in rat: An experimental study - Hassanali Abedi; Mahnaz Nemati; Bahare Ebrahimi; Maryam Dehghani; Elmira Mikaeiliagah; Pegah Abdollahzadeh; Aref Ghanaatpishe; Nazanin Shafiee Jahromi; Hossein Kargar Jahromi (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Cyclophosphamide (CP) is an anticancer drug that acts as an alkylation agent after metabolism in the liver. CP has toxic effects on the body's cells, especially the reproductive system's function, and causes infertility. Moreover, medicinal plants have few side effects and are psychologically acceptable to patients. Objective: This study aimed to investigate the impact of Ephedra pachyclada hydroalcoholic extract (EPHE) on ovarian tissue and hypothalamic-pituitary-gonadal axis in rats treated with CP. Materials and Methods: In this experimental study, 48 adult female Wistar rats (180-200 gr, 9-10 wk) were randomly assigned to 6 experimental groups (n = 8/each): (a) control; (b) sham; (c) CP; (d) CP+250 mg/kg EPHE; (e) CP+500 mg/kg EPHE; (f) CP+1000 mg/kg EPHE. On the 29 th day of the experiment, serum was collected; serum concentration of the luteinizing hormone, follicle-stimulating hormone, estrogen, progesterone, and antioxidant activity were measured. The number of ovarian follicles were also counted. Results: In the CP groups, serum concentrations of follicle-stimulating hormone and luteinizing hormone significantly increased, and estrogen and progesterone significantly decreased (p ≤ 0.05). EPHE significantly compensated for the complications caused by CP and 1000 mg/kg had the greatest effect. Antioxidant reduction by CP was significantly enhanced by EPHE, especially at higher doses (p ≤ 0.05). The number of primordial, primary, secondary, and Graafian follicles showed a significant decrease in CP groups and EPHE groups showed a significant increase compared to the CP. EPHE showed that the concentration of 1000 mg/kg was more effective than other doses (p ≤ 0.05). Conclusion: In addition to proving the effect of EPHE on the hypothalamic-pituitary-gonadal axis, our investigation showed antioxidant properties, which can be an effective factor in CP-treated rats.